Social context on an agreement letter of sri sultan paduka government of india nederland and the kingdom of bima - Diansyah, Nurrahman (International research journal of management, IT and social sciences, 2016)
The release of a treaty between Sri Sultan Paduka Government successor agreement Hindi Netherlands and the Kingdom of Bima is a related product. It means that a text of the letter agreement cannot be separated from the social context of the time. The theory of the social context LFS Hallidayan is adopted in a social context study. Data, collected from the literature and interview methods, are analyzed through the procedure of analyzing qualitative data instituted. The finding shows that a written agreement was made in an institutionalized situation in the kingdom of Bima involving both the Government of the India-Netherlands and the Kingdom of Bima. The Bima Kingdom became the emperor wrapper while the Hindi Netherlands government became the superior wrapper. The treaty governs the rights and obligations of both parties. This is written with regard to gender explanation of ideological hegemony, which includes the. Hindi Netherlands against the Bima Kingdom through the regulation of rights and obligations.